Intercultural competency and student travel - Sazli, Nor Sabirah; Sahar, Rafidah (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
Today, student travel represents one-fifth of all international arrivals in a travel industry, commanding a market value of $320 billion. More importantly, student travel facilitates increased intercultural contacts with people from different cultures than before. Against this background, this paper discusses the value of student travel for developing intercultural communication skills and competency. Intercultural communication is one’s ability to communicate and behave appropriately across cultures without violating social norms. Using a self-reported inventory modelled off of Deardorff Intercultural Competence framework (2006), an online survey was conducted with 105 undergraduates at a Malaysian university. Results revealed that female students appeared to be more open towards intercultural interaction than male. Moreover, students who were self-funded and traveled alone reported higher intercultural competency than others. This paper concludes that in today’s higher education context, student travel is one platform that can develop students' intercultural competency in an increasingly multicultural population.